Self-regulation of insect communities in agrocenoses of organic farming systems - V. Sabluk; N. Zapolska; K. Shendryk; V. Dimitrov (Карантин і захист рослин)
Goal. Establishing the effect of organic farming on the preservation of useful entomofauna in agrocenoses of winter wheat and sugar beet and determining its role in controlling the number of phytophages.